2020
DOI: 10.21547/jss.722344
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye Ekonomisi Açısından Benoit Hipotezinin Testi

Abstract: Savunma harcamaları, uluslararası platformda ülkelerin ekonomik ve siyasal sahadaki gücünün simgelerinden biri durumundadır. Küresel askeri kaygılara bağlı olarak, ülkelerin güvenliği açısından önemli bir parametre olan savunma harcamalarının rolü artmakta ve bu durumun da büyüme üzerinde etkileri olabilmektedir. Mevzubahis konu jeopolitik konumu gereği Türkiye için ayrıca önem ihtiva etmektedir. Bu çalışmada Benoit Hipotezi'nin geçerliliği Türkiye'nin 1980-2017 dönemi için araştırılmıştır. Bu bağlamda değişke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The Benoit Hypothesis was tested by Kanca and Yamak (2020) using the data for the Turkish economy from 1980 to 2017. Using ARDL co-integration and Toda-Yamamoto causality tests, the study found a long-term inverse relationship between economic development and defense expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Benoit Hypothesis was tested by Kanca and Yamak (2020) using the data for the Turkish economy from 1980 to 2017. Using ARDL co-integration and Toda-Yamamoto causality tests, the study found a long-term inverse relationship between economic development and defense expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It shows that this situation does not valid in Turkey. Kanca and Yamak (2020) examined the validity of the Benoit Hypothesis with data for the Turkish economy between 1980-2017. ARDL co-integration and Toda-Yamamoto causality tests are applied and a long-run negative connection among military expenditures and growth was detected in the study.…”
Section: Empirical Literature On the Relationship Between Economic Growth And Defense Expendituresmentioning
confidence: 99%